ATP11B deficiency leads to impairment of hippocampal synaptic plasticity. (1st June 2019) - Wang, Jiao; Li, Weihao; Zhou, Fangfang; Feng, Ruili; Wang, Fushuai; Zhang, Shibo; Li, Jie; Li, Qian; Wang, Yajiang; Xie, Jiang; Wen, Tieqiao
Abstract: Synaptic plasticity is known to regulate and support signal transduction between neurons, while synaptic dysfunction contributes to multiple neurological and other brain disorders; however, the specific mechanism underlying this process remains unclear. In the present study, abnormal neural and dendritic morphology was observed in the hippocampus following knockout of Atp11b both in vitro and in vivo . Moreover, ATP11B modified synaptic ultrastructure and promoted spine remodeling via the asymmetrical distribution of phosphatidylserine and enhancement of glutamate release, glutamate receptor expression, and intracellular Ca 2+ concentration. Furthermore, experimental results also indicate that ATP11B regulated synaptic plasticity in hippocampal neurons through the MAPK14 signaling pathway. In conclusion, our data shed light on the possible mechanisms underlying the regulation of synaptic plasticity and lay the foundation for the exploration of proteins involved in signal transduction during this process.